EFFECT OF RICE-STRAW COMPOST FERTILIZER ON THE YIELD PERFORMANCE OF SULAWESI LOCAL AROMATIC RICE IN INDONESIA - Kadir, Muhammad; Harsani, Harsani (ITScience (Information Technology and Science), 2022)
A field experiment evaluated the effect of different doses of composted organic fertilizer made from rice straw on the yield of three local aromatic rice varieties of Luwu Regency in the safe growing season (rainy season). The local aromatic rice varieties were Ngappa, Sassa, and Latimojong varieties, and four doses of composted organic fertilizer from rice straw, namely 0, 4, 8, and 16 tons/ha, were used as treatment variables. The experiment was laid out in a Completely Randomized Block Design (CRBD) with two factors and three replications. At harvest, data were collected on various characters that contributed to the yield of aromatic rice. The results showed no characters were affected by the interaction of variety and compost dosage. Ngappa variety produced the highest dry grain yield per hectare with 3,834 kg/ha, while the highest average production of local Sulawesi aromatic rice was with the application of 16 tons per hectare of rice straw compost in this experiment which produced 4,241.78 kg of paddy per hectare.